Increasing Consumption of Korean Dramas during the COVID-19 Pandemic: Cases of Indonesian Viewers - Yuliyanto Chandra (k@ta: A Biannual Publication on the Study of Languange and Literature, 2022)
This qualitative study focuses on Indonesian transnational fans’ consumption of Korean dramas (hereafter K-dramas) during the COVID-19 pandemic. This study highlights the fans’ lived experiences, thoughts, and interpretation of Korean culture in watching K-dramas as well as how they construct identities through their consumption and articulation in their everyday lives. This study used qualitative questionnaire as the instrument to collect the data for the study. Using thematic analysis, the study reveals that there were four emerging motivating factors to watch K-Dramas among Indonesian viewers: fresh substitutive choice, easy access, interesting stories and visuals, and cultural factors. Additionally, the study also showed four outcomes of their consumptive behavior: language acquisition and motivation to learn Korean, cultural understanding and new perceptions of Korea, pursuit of education, and pure entertainment and stress-reliever. Hence, this study contributes to the body of literature on K-Dramas consumption, especially in the era of COVID-19 pandemic.